"The stakes could not be higher": A mixed methods study of parental social media use in pediatric oncology. Issue 11 (16th June 2021) - Foot, Elizabeth; Leonhard, Amanda; Majeski, Jill; Zahn, Lauren; Li, Hsin H.; Caruso Brown, Amy E.
Abstract: Background: To describe how parents and families of children with cancer evaluate the benefits and risks of using social media (SM) and how they navigate disagreements between oncologists' advice and information found on SM. Procedure: Parents of children who had been previously diagnosed with cancer, and who had used SM for a purpose related to that child's health were recruited through SM sites and nonprofit organizations across the United States and were invited to complete questionnaires about their experiences using SM; a subset of participants also completed a follow‐up in‐depth interview. Open‐ended responses and interviews were analyzed using thematic analysis. Results: Ninety parents completed written questionnaires; 21 completed follow‐up interviews. Seventy percent reported experiencing a situation in which information shared on SM conflicted with information provided by their child's oncologist. Although 86% reported that they discussed the conflicting information with the oncologist and 70% described the oncologist's response as positive, 78% also described ongoing negative feelings about the experience. Parents described openness to discussing SM, honesty, transparency, and humility regarding the limits of medicine, and shared decision‐making regarding information found on SM as increasing their trust in their oncologist. Conclusions: Parents offered valuable insights regarding their experiences navigating SM, including eight recommendations for how pediatricians might approach discussing parental SM use. Future studies will evaluate the utility of these recommendations for pediatric clinicians.